University futures : Insights from a dialectic delphi study - Virmajoki, Veli; Ahlqvist, Toni; Suomalainen, Kaisa-Maria; Ahokas, Ira (Elsevier, 2026)
The future of universities is unclear. They face increasing pressures from market forces, political influence and societal expectations, which is challenging their traditional roles and values. Using a novel dialectic Delphi methodology, this study examined how members of a Finnish university conceptualized and analyzed potential futures extending to 2040. Grounded in a comprehensive literature review, we identified 10 dimensions relevant to universities’ futures, such as purpose, organisational structure and teaching models. We developed a series of statements presenting opposing future trajectories for each dimension—creating the dialectic nature of our approach. This structure was chosen to provoke reflection on distinct futures and to reveal whether participants saw opposing scenarios as incompatible or complementary. The participants assessed the probability and desirability of these futures and provided arguments to explain their perspectives. The findings identify where participants’ assessments of desirability and probability either align, conflict or reveal differing interpretations of the future scenarios and their meanings. This study reveals how university communities can be engaged in reasoning about complex institutional challenges while providing guidance for developing sustainable and balanced university futures.